From experiences to literacy, Literacy and playful practices in early Childhood Education - Léia Gonçalves de Freitas; Vilma Aparecida de Pinho; Marcia Lemos Braga (Universidade Federal do Norte do Tocantins, 2023)
The objective of the study is to systematize and socialize the experiences of a teacher of Early Childhood Education in a public school in the city of Uruará - PA, problematizing how practices have occurred in relation to the guidelines of the legal principles of the National Common Curricular Base (BNCC) regarding literacy and literacy in the Early Childhood Education stage. The methodological course was the Experience Report, based on Lüdke and Cruz (2010), understanding that, as a modality of academic-scientific writing, it contributes to the improvement and qualification of the construction and discussion of critical and reflective knowledge. In this sense, the teacher's report allowed us to point out that literacy and literacy are inseparable in the educational context of children, as they have their own impressions and interpretations of know-how. Thus, when exploring, feeling and acting, they elaborate, give senses and meanings to their experiences in different learning contexts.